2020
DOI: 10.1371/journal.pone.0238649
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative muscle mass restoration as a prognostic factor in patients with resected pancreatic cancer

Abstract: Background Recent studies have found that muscle depletion may be a prognostic predictor in patients with pancreatic cancer (PC). However, in these studies, limited data were used to assess the relationship between the serial change in body composition and outcomes after PC resection. Hence, we evaluated the changes in body composition during the perioperative period in patients with PC and their association with the overall survival (OS). Methods A total of 89 patients with PC who received surgery with curati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…4 Measuring the total cross-sectional area of the lumbar musculature is a reliable method to determine skeletal muscle composition, and as shown in previous cancer studies, has demonstrated prognostic utility. [5][6][7][8][9][10][11][12][13] However, this gold standard metric requires specialized training, expensive software, and is time consuming, all of which may potentially disturb the clinical workflow. 13 By contrast, measuring the linear area of the lumbar psoas and paraspinal musculature offers a reliable substitute, as it can be quickly performed and only requires a digital ruler tool found in virtually all radiologic software programs.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Measuring the total cross-sectional area of the lumbar musculature is a reliable method to determine skeletal muscle composition, and as shown in previous cancer studies, has demonstrated prognostic utility. [5][6][7][8][9][10][11][12][13] However, this gold standard metric requires specialized training, expensive software, and is time consuming, all of which may potentially disturb the clinical workflow. 13 By contrast, measuring the linear area of the lumbar psoas and paraspinal musculature offers a reliable substitute, as it can be quickly performed and only requires a digital ruler tool found in virtually all radiologic software programs.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 It has been widely established that preoperative skeletal muscle deficiency is associated with adverse outcomes in patients with various malignancies, including RCC, bladder cancer, and urothelial carcinoma. [6][7][8][11][12][13] However, these studies fail to consider the dynamic nature of skeletal muscle change during cancer and its associated treatments, and how continuous degeneration or potential recovery may influence a patient's clinical trajectory. 13,16 Studies that have evaluated postoperative muscle restoration have demonstrated its prognostic capability, but by contrast, have been among patients undergoing extirpative surgery for malignancies other than those of renal origin, such as pancreatic, 7 periampullary, 8 non-small cell lung, 9 gastric, 10 and oesophageal 11 cancer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations